Prediksi Kualitas Laporan Keuangan Kementerian Negara/Lembaga Menggunakan Machine Learning - Teguh Puspandoyo; Widha Adinata; Laode Atthar Alfikry; Tyas Ayu Prasanti; Silvi Yuniar (Direktorat Sistem Perbendaharaan, 2022)
Quality financial reports are one of the tools in realizing government accountability. However, not all State Ministries/Agencies yet have received the best opinion. Based on previous research, several factors have a significant influence on the quality of financial reports. Therefore, this study aims to analyze the influencing factors and also make predictions and classification of quality of state ministries/agencies of financial reports using machine learning techniques. The sample used in this study was 256 state ministries/agencies from 2018-2020. The results show that cash fraud, findings, follow-up to BPK's recommendations, the money supply/additional money supply, and realization have a strong influence in determining quality of financial reports. In addition, with the Support Vector Machine model, better classification predictions are obtained for quality of state ministries/agencies of financial reports.